2009
DOI: 10.1002/hyp.7516
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of the groundwater flow system of the Gumera sub‐basin in Lake Tana basin, Ethiopia

Abstract: Abstract:The groundwater flow contribution into Lake Tana was simulated using Gumera River sub-basin as a case study. Draining into Lake Tana, the Gumera sub-basin boundary was delineated from a 90-m Shuttle Radar Terrain Mapping (SRTM) digital elevation model (DEM) using ArcHydro tools. The sub-basin boundary served as the divide line of the groundwater flow while stream networks were used as internal drainage lines. Input parameters such as transmissivity and hydraulic conductivity were obtained from past st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Previous studies on Lake Tana showed that the groundwater contribution can be considered negligible [59,60]. Ref.…”
Section: Groundwater Inflow (G I ) and Outflow (G O )mentioning
confidence: 99%
“…Previous studies on Lake Tana showed that the groundwater contribution can be considered negligible [59,60]. Ref.…”
Section: Groundwater Inflow (G I ) and Outflow (G O )mentioning
confidence: 99%
“…Precipitation measurements obtained from climate hazards group infrared precipitation with stations (CHIRPS) products indicates that, long-term mean annual total rainfall ranges from 1250 mm/year at outlets of the watershed while it ranges to 15,440 mm/ year at inlets of the watershed around peaks of Mount Guna. Due to this, Guna-Tana watershed is an area that contributes large amount of runoff and sediment for Blue Nile River system through Gumera and Ribb rivers (Setegn et al 2008;Chebud and Melesse 2009). In its lower plains, there is encroaching irrigation activity and repeated flooding incidence caused by flood hazard from upper courses of the watershed (Woubet and Dagnachew 2011).…”
Section: Study Areamentioning
confidence: 99%
“…The surface elevation cannot be delineated by only using the borehole data because of the JUA's large area. Therefore, the JUA was delineated using the Shuttle Radar Terrain Mapping (SRTM) digital elevation model (DEM) data with 90 m resolution from the US Geological Survey (USGS) [33,34]. ArcGIS 10.0 software was used to reset the resolution of the SRTM DEM.…”
Section: Geological Modelmentioning
confidence: 99%